2021
DOI: 10.26710/jbsee.v7i3.1836
|View full text |Cite
|
Sign up to set email alerts
|

Review of Single National Curriculum with Perspective of the Education of Children with Visual Impairment at Primary Level in Punjab Pakistan

Abstract: Purpose: The Single National Curriculum (SNC) is one of the basic items of manifesto of ruling party in Pakistan.  The academic capability of Children with Visual Impairment (CWVI) is usually considered as that of non-disabled students due to their good cognitive skills. Directorate of Special Education Punjab adopted the same curriculum for CWVI. This study is an effort to identify the standards, benchmarks and SLOs which are difficult to accomplish for CWVI. It was a qualitative study by method and curriculu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…There is a noticeable gap between the pupils who attend these schools because of the significant disparities in the education that these three systems offer. The establishment of the SNC aimed to close the disparity that exists in the middle of the three different kinds of systems (Jahanzaib et al, 2021).…”
Section: Single National Curriculummentioning
confidence: 99%
“…There is a noticeable gap between the pupils who attend these schools because of the significant disparities in the education that these three systems offer. The establishment of the SNC aimed to close the disparity that exists in the middle of the three different kinds of systems (Jahanzaib et al, 2021).…”
Section: Single National Curriculummentioning
confidence: 99%
“…The study showed there was a significant value of parent participation in the learning of children with and without disabilities. In India, Jahanzaib and Fatima (2023) examined parental involvement among children with or without disability. The results also indicated that the parents of children with learning disability got involved in their immediate learning environment rather than the general school environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Document analysis is beneficial as it would enable researchers to organize or categorize non-numerical detailed data (Longo, 2019). The content of Oxford's social studies textbooks for the Primary classes from grades 1 to 5 was critically analyzed by using the document analysis technique and the reason behind the selection of Oxford textbooks is that they are developed on basis of the National Curriculum of Pakistan (Jahanzaib et al, 2021). Documents are a source of data or information while content analysis is used to analyze the contents of documents appropriately.…”
Section: Document Analysismentioning
confidence: 99%